Can an Awareness Campaign Boost the Effectiveness of Influencer Marketing Disclosures in YouTube Videos? - Sophie C. Boerman; Eva A. van Reijmersdal; Esther Rozendaal (Media and Communication, 2023)
Answering the strong need for insight into how minors can effectively be informed about advertising (e.g., influencer marketing) in online content, we ran an online experiment (N = 623 minors between 8 and 18 years old) testing the effects of two pictograms that were designed in co-creation with minors and the potential of an awareness campaign to boost the pictogram’s effectiveness. Our findings provide three important insights that have implications for theory, practice, and regulation. First, we find that minors are able to distinguish between sponsored and non-sponsored videos, indicating that they have developed some level of advertising literacy in this context. Second, our study shows that the two pictograms informing minors about advertising in online videos went unnoticed by most viewers and did not enhance conceptual or attitudinal advertising literacy. Third, the awareness campaign did not lead to higher recognition of the pictograms nor enhanced advertising literacy. The campaign did increase minors’ understanding of the meaning of the pictograms. However, the majority of minors also understood the pictograms without the campaign. Based upon our findings, we argue that pictograms are unnoticed by most minors and seem ineffective in enhancing minors’ advertising literacy. Although an awareness campaign can familiarize minors with pictograms and their implementation in online videos, it does not seem to boost the pictogram’s effects on advertising literacy.